Morphology and Formation of an Holocene Coastal Dune Field, Bruce Peninsula, Ontario - Davidson-Arnott, Robin; Pyskir, Natalia (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1988)
ABSTRACTThis paper describes a dune field on the gently-sloping Lake Huron shoreline of the Bruce Peninsula, Ontario. The inland boundary is marked by a prominent dune ridge 60 m wide and up to 30 m high, which extends parallel to the shoreline for about 19 km, and was formed about 5000 years BP near the end of the Nipissing transgression. The islands and rock reefs which protect the modern shoreline were submerged under the higher lake levels, giving rise to a relatively straight, exposed beach from which sediment was supplied for building the dune ridge. Dunes formed between this ridge and the modern shoreline during the post-Nipissing regression decrease in height and continuity, reflecting decreased sediment supply associated with regression and reduced wave exposure as the offshore islands emerged. The sequence described here supports previous conclusions that transgressions are associated with periods of coastal dune formation and instability.